A Comprehensive Analysis of Robustness in Interdependent Mechatronic Systems under Attack Strategies - Gang Xu; Yanhui Wang; Yucheng Hao; Limin Jia; Zeyun Yang; Zhichao He (Discrete Dynamics in Nature and Society)
With the development of mechatronic systems, different kinds of subsystems within them are highly correlated to each other due to the demand for the special function. To assess the robustness in the mechatronic system under various disturbances, we build an interdependent mechatronic system as an interdependent machine-electricity-communication network (IMECN) and adopt the improved cascading failure model where the occurrence of the failure propagation is decided by a proportion threshold δ. In order to fully explore the robustness under different disturbances, we develop attack strategies concerning nodes, edges, and interdependent links by considering measures for a node. Then, we also define the robustness metric to quantify the performance of IMECN during the entire attack process. The mass transit vehicle is taken as an example to investigate the impact of attack strategies on the robustness at different δ in a real-world mechatronic system. It is found that each subnetwork in this IMECN has a scale-free property. Based on simulation results, we obtain the most efficient attack strategies to remove nodes, edges, and interdependent links for different possibilities of triggering the failure propagation. In addition, we find that the attacks on nodes and interdependent links make IMECN more vulnerable compared with the ones on edges. This work provides theoretical insights into the comprehensive analysis of the robustness in interdependent mechatronic systems.